2018
DOI: 10.1007/s40258-018-0415-5
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Expert Judgement Across NICE Guidance-Making Programmes: A Review of Current Processes and Suitability of Existing Tools to Support the Use of Expert Elicitation

Abstract: ObjectivesThis study aimed to review current use of experts within National Institute for Health and Care Excellence (NICE) guidance-making programmes, identify improvements in use of expert judgement, and to assess tools and protocols to support the elicitation of information from experts for use by NICE.MethodsThe study comprised a review of NICE process guides; semi-structured interviews with individuals representing each NICE guidance-making programme and a comparison of the suitability of currently availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…10 In terms of SEE in health care, NICE uses expert judgement across all guidance-making programmes, but expert elicitation (vs. expert opinion) is used less frequently. 11 Existing timelines and consequent time constraints are reported as the common obstacles when conducting expert elicitation in health care. 11 There is an increasing interest in SEE, as HTAs are conducted progressively closer to the launch of the intervention of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In terms of SEE in health care, NICE uses expert judgement across all guidance-making programmes, but expert elicitation (vs. expert opinion) is used less frequently. 11 Existing timelines and consequent time constraints are reported as the common obstacles when conducting expert elicitation in health care. 11 There is an increasing interest in SEE, as HTAs are conducted progressively closer to the launch of the intervention of interest.…”
Section: Discussionmentioning
confidence: 99%
“…11 Existing timelines and consequent time constraints are reported as the common obstacles when conducting expert elicitation in health care. 11 There is an increasing interest in SEE, as HTAs are conducted progressively closer to the launch of the intervention of interest. 12 SEE is also essential for 'early modelling' of new interventions or unknown diseases for which little or no evidence is available.…”
Section: Discussionmentioning
confidence: 99%
“…Combining the literature review with the judgment of experts during guideline development is particularly important in fields in which less data are available on interventions and outcomes. 26 According to the current RCTs and meta-analyses, strategies for preventing inpatient falls in hospitals have relatively minor effects on the actual fall rates even when complex and multidisciplinary interventions are applied. 27 High-quality evidence for the effectiveness of fall prevention interventions in acute care settings is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Bojke et al (27) recently undertook an expert elicitation exercise to validate a new framework and this took 5 months of researcher time. Indeed, even in the relatively well-resourced environment at the National Institute for Health and Care Excellence (NICE), expert elicitation is often done informally (28). Our review identified a number of examples of the application of structured methods of stakeholder consultation, but studies have generally been undertaken in the context of a translational research body such as the Center for Translational Molecular Medicine (CTMM) (29;30).…”
Section: Methods Of Development-focused Htamentioning
confidence: 99%